Treatment of congenital middle ear cholesteatoma in children using endoscopic and microscopic ear surgeries: a case series - Xue, Po; Wang, Zhaoyan; Chai, Yongchuan; Si, Mingjue; Hu, Lingxiang (Frontiers in Pediatrics, 2024)
Surgical removal is widely employed in children with congenital middle ear cholesteatoma (CMEC). Here, we report the surgical outcomes of CMEC removal via endoscopic ear surgery (EES) and microscopic ear surgery (MES) in children. Children with CMEC who underwent preoperative medical history inquiry, hearing test, endoscopic evaluation, and radiology imaging before receiving EES or MES were included. Postoperative audiological outcomes and recurrence rates were collected. Seventeen children (20 ears) with stage II–IV CMEC were included. Of those, 11 ears (55.0%) underwent EES, and 9 ears (45.0%) underwent MES. The follow-up time was 35 ± 13.5 months. One child in the EES group with stage III CMEC had a recurrence during the follow-up period. In the EES group, the average minimum diameter of the external auditory canal on the affected side was 5.8 mm (4.3–8.0 mm). No linear association was found between age and the minimum diameter of the external auditory canal. EES is a promising treatment option for children with early-stage CMEC because of its low recurrence rate and minimally invasive nature. The minimum diameter of the external auditory canal on the affected side should be meticulously examined when performing EES in children.